Breaching or disturbing the peace? Organizational aesthetic encounters for informed and enlivened management learning experiences. Issue 2 (April 2015) - Mack, Kathy
The recent burgeoning of "organizational aesthetics" scholarship represents unrealized potential for transforming management learning practices. In response to calls for more embodied "holistic" ways of knowing, the present case study is a "wayfinding" journey into organizational aesthetic encounters with undergraduate management students. Initial encounters reveal how narratives of organizational quotidian evoke aesthetic attunement. Closer encounters engage students with their own aesthetic inquiries and artifacts to re-present aesthetic knowledge and sensibilities. As aesthetically attuned and active producers of "organizational aesthetics, " what is sensible and thus knowable in the context of management learning is disturbed—informing and enlivening our learning experiences. From a practical standpoint, these types of aesthetic encounters may breach the "management learning" peace, one disturbance at a time.